Road pavement material characterization and rehabilitation : selected papers from the 2009 GeoHunan International Conference, August 3-6, 2009, Changsha, Hunan, China - Steyn, Wynand JvdM; Jenkins, Kim J.; Solaimanian, Mansour; American Society of Civil Engineers. Geo-Institute (USA : American Society of Civil Engineers, 2009)
08